ANALISIS PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP OPINI AUDIT GOING CONCERN - Abdurrachman Abdurrachman; Rizky Amalia; Bryan Givan (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2021)
Companies that receive a going concern audit opinion show events and conditions that would cause the auditor to doubt about the going concern of the company. This opinion can be used as an initial signal for users of financial statements to avoid mistakes when making a decision. Regarding the factors that influence going-concern audit opinion, many previous studies have been carried out. However, it has inconsistencies in the results of the study. Thus, the research aims to carry out retesting related "factors that influence going concern audit opinion". The variables tested include Profitability and Liquidity. The research sample uses manufactur companies in the consumer goods industry which were listed on the Indonesian Stock Exchange for the period 2018-2019. The sampling technique was purposive sampling, which obtained 102 companies’ data that matched the criteria. Logistic regression analysis was used to test the hypothesis of this study. Hypothesis testing results that partially the profitability and liquidity variables have no effect on going-concern audit opinion.